An immunoprotective molecule, the major secretory protein of Legionella pneumophila, is not a virulence factor in a guinea pig model of Legionnaires' disease. - Blander, S J (1990)
We have examined whether a molecule that is capable of inducing immune protection, the major secretory protein (MSP) of Legionella pneumophila, is required for virulence in a guinea pig model of Legionnaires' disease. To do so, we have compared the virulence in guinea pigs of an isogenic pair of L. pneumophila, Philadelphia 1 strain, one of which produces MSP (MSP+) and one of which does not (MSP-). Both the MSP- strain and the MSP+ strain of L. pneumophila are highly virulent for guinea pigs, inducing similar signs and progression of illness. Both strains are lethal and have comparable LD50s and LD100s. Both strains multiply in the lungs of guinea pigs at a similar rate, and both strains produce indistinguishable pathological lesions in the lungs. Both strains maintain a stable phenotype with guinea pig passage, i.e., the MSP- strain does not regain the capacity to secrete MSP and the MSP+ strain retains its capacity to secrete MSP after lung passage. Although vaccination with MSP induces strong protective immunity in the guinea pig against lethal aerosol challenge with L. pneumophila, this protective immunogen is not required in its intact proteolytically active form for the expression of virulence by the intracellular pathogen L. pneumophila. This demonstrates that a protective immune response need not necessarily be directed against a virulence determinant and suggests that any molecule that allows the host immune system to detect and act against an intracellularly sequestered pathogen may potentially serve as a protective immunogen against such a pathogen.